Inisiasi AMIS Integrated Farming Melalui Kelompok Peternak Ayam Petelur Menuju Pertanian Berkelanjutan - Huda, Khoirul; Siswara, Hamzah Nata; Zuhdi, AH. Maftuh Hafidh; Mubarok, Amin; Dana, Aldi Arma (Jurnal Pengabdian Masyarakat Charitas, 2024)
The existence of layer poultry farmer groups faces challenges in the era of global climate change. The rise in environmental temperatures significantly impacts agricultural and livestock activities. On the other hand, livestock farming generates a considerable amount of organic waste, which poses environmental concerns. The goal of the integrated farming system based on chickens, maggots, fish, and vegetables (AMIS) is to encourage resilient farmers to face global climate change, achieve zero waste agriculture and livestock farming, and establish a circular economy. The methods applied in the implementation of this program is socialization, training, and system application assistance. Participants from the Sumber Unggas Jaya Livestock Farmers Group were very enthusiastic about participating in every activity. This was demonstrated by their active involvement in each event and discussion. The participants also expressed interest in applying the AMIS system to their existing farming operations. This system can reduce organic waste pollution through the zero waste concept, increase income through the circular economy concept, and make agricultural and livestock activities resilient to global climate change by forming a sustainable plant and livestock maintenance ecosystem.